2019
DOI: 10.3329/bjz.v47i1.42022
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of intestinal parasites among school going children of a slum area in Dhaka city

Abstract: A cross sectional study was carried out among school going children of Ganaktuli slum area in Dhaka city, Bangladesh. A total of 183 stool samples were collected from children of age between 5 and 16 years of both sexes during May, 2017 to April, 2018. Collected samples were examined using Formal-Ether Concentration technique. 61.20% samples were found positive for intestinal parasites. Eight species of parasites were identified, where Entamoeba histolytica (3.83%), Giardia lamblia (6.01%), Diphyllobothrium la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
4
2
Order By: Relevance
“…histolytica/ dispar in this meta-analysis was 13.3%, which is consistent with the 14.09% rate reported in Ethiopia [ 4 ] and 12.1% in the Philippines [ 78 ]. However, the prevalence rate in the present study was lower than that in studies conducted in Malaysia (20.4%) [ 79 ], Yemen (16.4) [ 80 ] and Tanzania 15% [ 81 ] but higher than that in studies in Bangladesh (3.83%) [ 82 ] and Thailand (3.7%) [ 83 ].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…histolytica/ dispar in this meta-analysis was 13.3%, which is consistent with the 14.09% rate reported in Ethiopia [ 4 ] and 12.1% in the Philippines [ 78 ]. However, the prevalence rate in the present study was lower than that in studies conducted in Malaysia (20.4%) [ 79 ], Yemen (16.4) [ 80 ] and Tanzania 15% [ 81 ] but higher than that in studies in Bangladesh (3.83%) [ 82 ] and Thailand (3.7%) [ 83 ].…”
Section: Discussioncontrasting
confidence: 88%
“…Similar infection rate (11.0%) was reported from Brazil [ 84 ], and a considerably higher prevalence rate was detected in Nepal (46.8%) [ 85 ]. Meanwhile, the infection rate in Bangladesh (6.01%) [ 82 ] and Thailand (4.9%) [ 83 ] was lower than the present finding. The variations in prevalence rates of E .…”
Section: Discussioncontrasting
confidence: 87%
“…On the other hand, Shreshtha et al have reported 39.7% of IPIs among school children of two schools from central Nepal [18]. Similarly, very high rates of IPIs were reported in school children from different countries [21][22][23][24]. Another study from Morang, a neighbour district of Saptari, reported 83.3% of stool samples with helminth parasites in school children where A. lumbricoides (50.92%) was the most detected parasite followed by Ancylostoma duodenale (44.56%) and Trichuris trichiura, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…A study among pediatric patients (below five years) in a tertiary hospital was done where Giardia cysts were found in 4.14% of cases [ 107 ]. In a slum area of Bangladesh, Giardia duodenalis positive samples were found in 6.01% of cases among school-going children [ 108 ]. In Sikkim, India, a prospective study among symptomatic children (<15 years) was done where Giardia cysts were found in 5% of cases by wet mount [ 109 ].…”
Section: Discussionmentioning
confidence: 99%